Osteology of Hemigrammocypris neglecta (Teleostei: Cypriniformes) with comments on its systematic position - Ito, Taiki; Hoshino, Kazuo; Hosoya, Kazumi (Zootaxa, 2021)
Hemigrammocypris neglecta is a small-sized cyprinid fish that is endemic to Japan and the sole member of the genus Hemigrammocypris. We examined the osteological features of the species, and its relationships with related genera are discussed. The present data suggest that H. neglecta is most likely the sister taxon of Metzia lineata. This relationship is supported by one possible synapomorphy: the presence of a postepiphysial fontanelle, which is absent in all other Xenocypridinae.